Perceived Stress and Perceived Lack of Control of Student Teachers in Field Practice Placements in Schools during the COVID-19 Pandemic: Validity of the PSS-10 Adapted to the Field Practice Context - Tine Nielsen (MDPI AG, 2023)
Field practice placements contribute substantially to students' gradual attainment and final mastery of the skills of the teaching profession. The aim of this study was to adapt the Danish consensus translation of the PSS-10 to assess perceived stress during field practice placements of varying durations and to investigate its validity for use with student teachers in field practice during the COVID-19 pandemic. Data were collected upon completion of 6 weeks of a field placement at one of three levels (N = 359), and grades from the field practice exam were obtained. To resolve any issues with differential item functioning and lack of item independence, graphical loglinear Rasch models were used. Criterion validity was investigated in relation to the level of field practice and subsequent grades. The results showed that items 10 and 4 had to be eliminated; both subscales had locally dependent items, and one item in the perceived lack of control subscale functioned differentially relative to the level of field practice placement. Criteria expectations were confirmed, though not all were significant. The psychometric properties of the adapted PSS-10 were in line with previous findings on the original PSS-10 subscales. Score levels can be used as benchmarks in post-COVID-19 studies of student teachers' field-practice-related perceived stress.